Identification of static surface form errors from cutting force distribution in flat-end milling processes - KURT, MUSTAFA (SPRINGER HEIDELBERG, 2015)
This paper presents a new and practical process simulation method to analyze surface errors caused by deflections of statically flexible flat-end mills. Milling force and surface error models are established to predict the surface error in various cutting conditions. The milling forces are predicted from the mechanistic model extended using the force distribution determined with an effective calibration procedure carried out by experimentally dividing the cutting part of the end mill into discs. The surface errors are modeled by establishing an analytical relationship between bending moments and deflections by means of the cantilever beam theory. These features make the present method very practical and efficient. A set of computational studies and experiments is performed to validate the effectiveness of the presented method. Comparisons of the results obtained numerically and experimentally confirm that the method is capable of accurate prediction of milling forces and surface errors. Finally, this method can be effectively applied for identifying appropriate cutting conditions in flat-end milling.
Keywords: Cutting tool deflection; Flat-end milling; Milling force; Surface error; CUTTER DEFLECTION; PREDICTION